Receiving social support motivates long-term prosocial behavior - Trombini, Chiara (Journal of business ethics, 2025)
Prosocial behavior—actions aimed to benefit other individuals, groups, or communities—are important for promoting and maintaining a healthy society. Extant research on the factors driving prosocial behavior has mainly addressed short-term effects, overlooking the factors that motivate long-term prosocial behavior. Building on attachment theory, we theorize that an interpersonal factor, receiving social support, can foster prosocial behavior in the long-term, both in the environment where the support was received and beyond it. We argue that receiving social support positively predicts felt security—a sense of being safe, cared for, and loved—which in turn associates with higher motivation to engage in behaviors that benefit others. We test our hypotheses with cross-sectional, longitudinal, retrospective, and experimental data. In Study 1, data from a sample of international business school alumni validate past research and show a significant positive relationship between receiving social support and engaging in prosocial behavior both within and beyond the environment in which support was received. Study 2 leverages data of US adults in a multi-wave study to show that receiving social support predicts prosocial activities several years later. Study 3 uses a retrospective survey to show that receiving social support relates positively to long-term prosocial behavior through higher felt security. Study 4 experimentally manipulates social support and further demonstrates that receiving social support fosters prosocial behavior through boosting felt security. Overall, our findings show that receiving social support motivates long-term prosociality through its positive association with felt security.